SPECT/CT imaging of lower extremity perfusion reserve: A non-invasive correlate to exercise tolerance and cardiovascular fitness in patients undergoing clinically indicated myocardial perfusion imaging - Chou, Ting-Heng (J Nucl Cardiol, 2020)
BACKGROUND: Although exercise is often prescribed for the management of cardiovascular diseases, a non-invasive imaging approach that quantifies skeletal muscle physiology and correlates with patients’ functional capacity and cardiovascular fitness has been absent. Therefore, we evaluated the potential of lower extremity single photon emission computed tomography (SPECT)/CT perfusion imaging as a non-invasive correlate to exercise tolerance and cardiovascular fitness. METHODS: Patients (n = 31) undergoing SPECT/CT myocardial perfusion imaging underwent additional stress/rest SPECT/CT imaging of the lower extremities. CT-based image segmentation was used for regional quantification of perfusion reserve within the tibialis anterior, soleus, and gastrocnemius muscles. Metabolic equivalents (METs) at peak exercise and heart rate recovery (HRR) after exercise were recorded. RESULTS: Peak METs were significantly associated with perfusion reserve of tibialis anterior (p = 0.02), soleus (p = 0.01) and gastrocnemius (p = 0.01). HRR was significantly associated with perfusion reserve of the soleus (p = 0.02) and gastrocnemius (p = 0.04) muscles. Perfusion reserve of the tibialis anterior (40.6 ± 20.2%), soleus (35.4 ± 16.7%), and gastrocnemius (29.7 ± 19.1%) all significantly differed from each other. CONCLUSIONS: SPECT/CT imaging provides regional quantification of skeletal muscle perfusion reserve which is significantly associated with exercise tolerance and cardiovascular fitness. Future application of SPECT/CT may elucidate the underlying skeletal muscle adapations to exercise therapy in patients with cardiovascular diseases. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12350-019-02019-w) contains supplementary material, which is available to authorized users.